Epithelium-Specific Ets-Like Transcription Factor 1, ESE-1, Regulates ICAM-1 Expression in Cultured Lung Epithelial Cell Lines - Zhiqi Yu; Jun Xu; Jinbao Liu; Jing Wu; Chan Mi Lee; Li Yu; Jim Hu (Hindawi Limited, 2015)
Cystic fibrosis (CF) patients suffer from chronic airway inflammation with excessive neutrophil infiltration. Migration of neutrophils to the lung requires chemokine and cytokine signaling as well as cell adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1), which plays an important role in mediating adhesive interactions between effector and target cells in the immune system. In this study, we investigated the relationship between ICAM-1 and epithelium-specific ETS-like transcription factor 1 (ESE-1) and found that ICAM-1 expression is upregulated in cell lines of CF (IB3-1) as well as non-CF (BEAS-2B and A549) epithelial origin in response to inflammatory cytokine stimulation. Since ESE-1 is highly expressed in A549 cells without stimulation, we examined the effect of ESE-1 knockdown on ICAM-1 expression in these cells. We found that ICAM-1 expression was downregulated when ESE-1 was knocked down in A549 cells. We also tested the effect of ESE-1 knockdown on cell-cell interactions and demonstrate that the knocking down ESE-1 in A549 cells reduce their interactions with HL-60 cells (human promyelocytic leukemia cell line). These results suggest that ESE-1 may play a role in regulating airway inflammation by regulating ICAM-1 expression.